A new approach based on the modified FDS to numerically simulate cardboard box combustion under low pressure. (13th November 2019) - Zhou, Rui; Zhao, Han; Ye, Junjian; Zhang, Hui
Summary: To solve the limitation of the fire test in high‐altitude areas only detecting a limited number of low‐pressure environments, in this paper, appropriate modifications of the FDS source codes were made to generate a new simulator program for low‐pressure applications. Standard fire experiments with different counts (1, 2, 18, and 27) of cardboard boxes were numerically simulated under different pressure levels (101, 90, 75, and 64 kPa). The computation data show consistent trends with the experimental results obtained in the low‐pressure tank at Lang Fang. Furthermore, the simulation results have been examined to show typical quantitative relationships: (a) The peak mass burning rate divided by the fire base dimension is correlated with the product of the pressure squared and the combustible characteristic length cubed. The exponential indices for the 1‐box fire, 18‐box fire, and 27‐box fire are 0.31, 0.29, and 0.29, respectively. (b) The heat release rate and mass burning rate show a good linearity at each fixed environmental pressure. In conclusion, the modified FDS is validated to work well under low‐pressure conditions, which can provide a receivable means to conduct low‐pressure fire simulation and analysis.